(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2023)
Ways of the Sacred in the World: Priceasna- the Connector between the Human and the Divine. A Sacred life is preffered to a Profane one, but this is impossible to apply in practice. What people could do instead, is to take a few elements of sacred life into their own profane existence. Such an element is the Romanian religious hymn, known as priceasna. The text and the melody of the „priceasna” are composed in order to invite people to pray and to reconnect with the Divinity in a perfect symbiosis. Written in a very simple way, it is meant to transcend the darkest corners of the human soul and to bring the light all over.